A chemical study of the glycoside of Plumiera acutifolia Ait. (Family Apocynaceae) - Montojo, Corazon P.; Castillo, Amorita V. (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
The fresh bark of the plant Plumiera actutifolia Ait. (Fam. Apocynaceae) was found to contain the bitter principle, plumieride. The sample was analyzed and subjected to thin layer chromatogrphy, column chromatography and spectrophotometry.
The following were obtained as a result of the tests performed on the sample: moisture content was 75.6666%. The crystals did not melt but decomposed at 220°C.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1978.
Keywords: Plumeria; Kalachuche